Faktor Determinan atas Profitabilitas Perbankan yang Terdaftar di Bursa Efek Indonesia - Alindra Yanuardi; Djumilah Hadiwidjojo; Sumiati (Jurnal Akuntansi Multiparadigma, 2014)
The purpose of this study is to analyze the influence of credit risk, liquidity risk, efficiency management, capital, inflation, and gross domestic product on banks profitability in 2010-2012. By using purposive sampling technique, 28 banks were obtained as sample of the study. The method of data analysis used is multiple linear regression analysis. The analysis showed that the credit risk, capital, inflation have significant and positive influence on bank profitability. Efficiency management has significant and negative influence on bank profitability. Liquidity risk and gross domestic product have no effect on bank profitability.